THE MEDIATING EFFECT OF EMOTIONAL ATTACHMENT BETWEEN SOCIAL MEDIA INTERACTIVITY AND WORD OF MOUTH - Vidyarini Dwita; Megawati Megawati (Politeknik APP Jakarta, 2021)
The purpose of this research was to investigate the role that emotional attachment plays as intervening in the relationship between social media interactivity and word-of-mouth in the context of coffee shop social media. The total number of respondents was 200, and the analysis of the data was performed with PLS Smart 13, which included both the reliability test and structural equation modelling. The results of this study suggested that there is a mediating impact of emotional attachment between social media interactivity and the word of mouth generated by coffee shop social media on Instagram. This is accomplished by developing a model that reflects on consumers' emotional attachment to brands and effect to electronic word of mouth, with particular focus on coffee shops' use of social media in Indonesia. The antecedents are something that can be taken into consideration for future social media word of mouth efforts in order to improve the word of mouth that customers give in the future.